2020
DOI: 10.1158/2326-6066.cir-19-0522
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Tumor Exosomes Drive Immune Escape in Melanoma

Abstract: ◥MicroRNAs (miRNA), small noncoding RNAs that regulate gene expression, exist not only in cells but also in a variety of body fluids. These circulating miRNAs could enable intercellular communication. miRNAs are packaged in membrane-encapsulated vesicles, such as exosomes, or protected by RNA-binding proteins. Here, we report that miRNAs included in human melanoma exosomes regulate the tumor immune response. Using microscopy and flow cytometry, we demonstrate that CD8 þ T cells internalize exosomes from differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 42 publications
2
94
1
Order By: Relevance
“…In the TME, immune cells including lymphocytes, dendritic cells, and macrophages, regularly infiltrate tumor tissues and adjacent sites. Through multiple signal transduction pathways mediated by exosomal miRNAs, tumor cells can inhibit the maturation and differentiation of immune cells, thereby creating an immune microenvironment suitable for tumor growth [41,137,138]. At the same time, in hypoxia and low nutrient supplies in the microenvironment, tumor cells often secrete metabolic by-products, such as lactic acid, nitric oxide, reactive oxygen species, prostaglandins and arachidonic acid, leading to the formation of an inflammatory microenvironment [139,140].…”
Section: Promoting the Formation Of Immunosuppressive Environmentmentioning
confidence: 99%
“…In the TME, immune cells including lymphocytes, dendritic cells, and macrophages, regularly infiltrate tumor tissues and adjacent sites. Through multiple signal transduction pathways mediated by exosomal miRNAs, tumor cells can inhibit the maturation and differentiation of immune cells, thereby creating an immune microenvironment suitable for tumor growth [41,137,138]. At the same time, in hypoxia and low nutrient supplies in the microenvironment, tumor cells often secrete metabolic by-products, such as lactic acid, nitric oxide, reactive oxygen species, prostaglandins and arachidonic acid, leading to the formation of an inflammatory microenvironment [139,140].…”
Section: Promoting the Formation Of Immunosuppressive Environmentmentioning
confidence: 99%
“…In melanoma patients, the plasma levels of miR-181a were higher in patients at diagnosis compared to controls, and the development of metastasis has been associated with changes in immune effector and regulatory cells with changes in plasma and cellular levels of immune regulatory miRNA [ 98 ]. Melanoma-derived exosomes decrease TNFα secretion in CD8+ cells and are enriched for hsa-miR-181a, which is capable of interacting directly with the 3′-UTR sequence of TNFα and driving immune escape in melanoma [ 99 ]. We have previously shown in our laboratory that overexpression of miR-181a negatively regulates IFN-γ expression in activated PB CD4+ T cells by directly binding to its target sites in the mRNA and increases the expression of IL4 [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once released by parent cells, exosomes can interact with neighboring or distant cell via at least three mechanisms [ 13 ]: (i) interaction between exosome transmembrane proteins and the signaling receptors of recipient cells, (ii) exosome fusion with the plasma membrane of recipient cell and release of their content into the cytosol, (iii) exosome internalization into the recipient cell by endocytosis. Interestingly, it has been shown that exosomal miRNAs released in the cytoplasm are functional and may induce function and phenotype changes in recipient cells [ 6 , 14 ].…”
Section: Exosome Biogenesis and Secretionmentioning
confidence: 99%
“…TEXs also facilitate progression, invasion, angiogenesis, metastasis and drug resistance. Some studies suggest that it could be due to the transfer of microRNAs (miRNAs) from tumor to recipient cells since they are largely enriched into exosomes [ 5 , 6 ]. miRNAs are a subset of small non–coding RNAs (from 19 to 22 nucleotides) known to regulate gene expression at the post–transcriptional level through mRNA silencing or degradation.…”
Section: Introductionmentioning
confidence: 99%